SURGICAL CORRECTION OF DYSTOCIA DUE TO HYDROCEPHALOUS FOETUS WITH EMPHYSEMA - KRISHNA, N VENKTA; BRAMHAIAH , K VEERA (The Indian Journal of Animal Reproduction, 2021)
The foetal abnormalities are one of the protagonists causes for causing parturient related issues ultimatelyresulting in dystocia. Several congenital deformities observed in cattle and buffaloes among those hydrocephalus,bulldog calf conditions are common. Pregnant cross breed Jersey cow aged 5 years presented to Teaching VeterinaryClinical Complex, College of Veterinary Science Tirupati with difficulty in parturition. Animal was showing symptoms ofparturition since 12 hrs and treated by local veterinarian. On per vaginal examination cervix was fully opened and thefoetus could not be delivered through birth canal and on detailed examination it revealed a marked enlargement ofcranial part of the head with emphysematous body. Based on this clinical and obstetrical examination the case wasdiagnosed as dystocia due to foetal hydrocephalous.
Keywords: Hydrocephalus; foetus; dystocia and emphysematous body